The isoprenoid derivative N6‐benzyladenosine CM223 exerts antitumor effects in glioma patient‐derived primary cells through the mevalonate pathway. (11th June 2017) - Ciaglia, Elena; Grimaldi, Manuela; Abate, Mario; Scrima, Mario; Rodriquez, Manuela; Laezza, Chiara; Ranieri, Roberta; Pisanti, Simona; Ciuffreda, Pierangela; Manera, Clementina; Gazzerro, Patrizia; D'Ursi, Anna Maria; et al.
Abstract : Background and Purpose: N 6 ‐Isopentenyladenosine (i6A) is a modified nucleoside exerting in vitro and in vivo antiproliferative effects. We previously demonstrated that the actions of i6A correlate with the expression and activity of farnesyl pyrophosphate synthase (FPPS), a key enzyme involved in the mevalonate (MVA) pathway, which is aberrant in brain cancer. To develop new anti‐glioma strategies, we tested related compounds exhibiting greater activity than i6A. Experimental Approach: We designed and synthesized i6A derivatives characterized by the introduction of diverse chemical moieties in the N6 position of adenosine and tested for their efficacy in U87 cells and in primary glioma cultures, derived from patients. NMR‐based structural analysis, molecular docking calculations and siRNA mediated knockdown were used to clarify the molecular basis of their action, targeting FPPS protein. Key Results: CM223, the i6A derivative including a benzyl moiety in N6 position of adenine, showed marked activity in selectively targeting glioma cells, but not normal human astrocytes. This was due to induction of intrinsic pathways of apoptosis and inhibition of proliferation, along with blockade of FPPS‐dependent protein prenylation, which counteracted oncogenic signalling mediated by EGF receptors. Conclusion and Implications: The biological effects together with structural data on interaction of CM223 with FPPS, provided additional evidence for the correlation of the i6A/CM223 antitumor activity with FPPS modulation. Because the MVA pathway is an important promising target, CM223 and its derivatives should be considered interesting active molecules in antiglioma research.